Palvelutuonti ja palvelujen siirrot ulkomaille - Ali-Yrkkö Jyrki; Kuosmanen Natalia (The Research Institute of the Finnish Economy (ETLA), 2023)
– According to our results the imports of services to Finland have increased. The share of services in total imports in Finland is relatively large compared to many other EU countries. Companies often use imported services as their intermediates, with services accounting for nearly half of the total intermediate imports. It seems that offshoring of services is declining. While in the years 2015-2017 approximately 8.5 % of large and medium-sized service companies offshored their operations abroad, in 2018-2020 the share had decreased to 6.4 %.
Keywords: F14; L8; 330; Service; Outsourcing; Offshoring; Internationalization; Intermediate good